The scientific impotence excuse in education – Disentangling potency and pertinence assessments of educational research - Futterleib, Holger; Thomm, Eva; Bauer, Johannes (Frontiers in Education, 2022)
When facing belief-contradictory scientific evidence, preservice teachers tend to doubt the potency of science and consult scientific sources less frequently. Thus, individuals run the risk to not only maintain questionable assumptions, but also to develop dysfunctional stances toward research as a reliable source of knowledge. In two studies, we (a) replicated findings on the so-called scientific impotence excuse (SIE) in education and (b) differentiated the effects on the potency and pertinence of science to investigate educational topics to better understand the nature of SIE-related science devaluation. Both studies followed a 2x2 mixed experimental design: Preservice teachers assessed their prior belief about an educational topic (i.e., effectiveness of grade retention) before and after reading either confirming or disconfirming scientific evidence concerning the topic. Study 1 (N = 147 preservice teachers; direct replication) confirmed the central prior findings of science devaluation when belief-evidence conflicts occur. In contrast, the results of Study 2 (N = 152; follow-up study) revealed no systematic devaluations of science when disentangling the facets of potency and pertinence. Despite partial devaluation tendencies, both studies revealed that preservice teachers adapted their prior beliefs to the evidence presented. These findings extent previous research by providing insights into the conditions of science devaluation.